Nitrogen Fertilizer Timing and Phosphorus and Potassium Fertilization Rates for Established Endophyte-Free Tall Fescue: Year 3 - D. W. Sweeney; J. K. Farney; J. L. Moyer; D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2021)
Tall fescue production was measured during the third production year of a study with locations started in fall of 2016 and fall of 2017. Phosphorus (P) fertilization rate affected spring harvest yield at Site 1, but not at Site 2. Applying nitrogen (N) in late fall or late winter resulted in greater spring yields than applying N in spring or not applying N. However, fall harvest yields at Site 1 were greater with spring N application, but not at Site 2. The third-year tall fescue total yield rank as affected by N fertilizer timing was late winter>late fall=spring>no N at Site 1 and late winter=late fall>spring>no N at Site 2.
Keywords: Nitrogen; phosphorus; potassium; tall fescue